Temperature and curing time affect composite sorption and solubility - Fabricio Luscino Alves de Castro; Bruno Barbosa Campos; Kely Firmino Bruno; Rogerio Vieira Reges (University of São Paulo, 2013)
Objective: This study evaluated the effect of temperature and curing time on composite sorption and solubility. Material and Methods: Seventy five specimens (8×2 mm) were prepared using a commercial composite resin (ICE, SDI). Three temperatures (10°C, 25°C and 60°C) and five curing times (5 s, 10 s, 20 s, 40 s and 60 s) were evaluated. The specimens were weighed on an analytical balance three times: A: before storage (M1); B: 7 days after storage (M2); C: 7 days after storage plus 1 day of drying (M3). The storage solution consisted of 75% alcohol/25% water. Sorption and solubility were calculated using these three weights and specimen dimensions. The data were analyzed using the Kruskal-Wallis and Mann-Whitney U Tests (α=5%). Results: The results showed that time, temperature and their interaction influenced the sorption and solubility of the composite (p<0.05). At 60°C, the composite sorption showed an inverse relationship with the curing time (p<0.05). The composite cured for 5 s showed higher sorption for the 40 s or 60 s curing times when compared with all temperatures (p<0.05). Curing times of 20 s and 40 s showed similar sorption data for all temperatures (p>0.05). The 60°C composite temperature led to lower values of sorption for all curing times when compared with the 10°C temperature (p<0.05). The same results were found when comparing 10°C and 25°C (p<0.05), except that the 20 s and 40 s curing times behaved similarly (p>0.05). Solubility was similar at 40 s and 60 s for all temperatures (p>0.05), but was higher at 10°C than at 60°C for all curing times (p<0.05). When the composite was cured at 25°C, similar solubility values were found when comparing the 5 s and 10 s or 20 s and 40 s curing times (p>0.05). Conclusions: In conclusion, higher temperatures or longer curing times led to lower sorption and solubility values for the composite tested; however, this trend was only significant in specific combinations of temperature and curing times.